2020
DOI: 10.3390/cancers13010080
|View full text |Cite
|
Sign up to set email alerts
|

The ITIM-Containing Receptor: Leukocyte-Associated Immunoglobulin-Like Receptor-1 (LAIR-1) Modulates Immune Response and Confers Poor Prognosis in Invasive Breast Carcinoma

Abstract: Background: The leukocyte-associated immunoglobulin-like receptor-1 (LAIR-1) plays a role in immune response homeostasis, extracellular matrix remodelling and it is overexpressed in many high-grade cancers. This study aimed to elucidate the biological and prognostic role of LAIR-1 in invasive breast cancer (BC). Methods: The biological and prognostic effect of LAIR-1 was evaluated at the mRNA and protein levels using well-characterised multiple BC cohorts. Related signalling pathways were evaluated using in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…One such study, for example, has shown that reducing tumor stiffness and collagen organization via inhibition of the collagen-crosslinking enzyme lysyl oxidase (LOX) increased T cell migration, tumor infiltration with CD8 + T cells, and antitumor activity of PD-1 blockade therapy in a model of murine pancreatic cancer ( 32 ). In addition to providing a physical obstacle to immune cells, collagens can also bind to the inhibitory receptor LAIR-1, which is expressed across multiple immune cell subsets ( 33 ) and correlates with poor prognosis in several tumor types ( 34 , 35 ). LAIR-1 signaling has been shown in preclinical models to drive T cell suppression and a TIM-3 + exhausted T cell phenotype that mediates resistance to ICB ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…One such study, for example, has shown that reducing tumor stiffness and collagen organization via inhibition of the collagen-crosslinking enzyme lysyl oxidase (LOX) increased T cell migration, tumor infiltration with CD8 + T cells, and antitumor activity of PD-1 blockade therapy in a model of murine pancreatic cancer ( 32 ). In addition to providing a physical obstacle to immune cells, collagens can also bind to the inhibitory receptor LAIR-1, which is expressed across multiple immune cell subsets ( 33 ) and correlates with poor prognosis in several tumor types ( 34 , 35 ). LAIR-1 signaling has been shown in preclinical models to drive T cell suppression and a TIM-3 + exhausted T cell phenotype that mediates resistance to ICB ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Joseph et al showed that LAIR-1 highly expressed at mRNA and protein levels was a signi cant factor in breast cancer-speci c survival (BCSS) and distant metastasis-free independent predictors of poor survival for distant metastasis-free survival (DMFS), unaffected by other complicating prognostic elements including tumor size, tumor grade, stage, CD3+, CD8+, HER2+ status, and chemotherapy (Joseph et al, 2020). Peng et al showed that LAIR-1 is a potential marker of ICIs in lung cancer (Peng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Four different types of ligands are described, including components of the complement system and collagens, suggesting a potential immune-regulatory function of the extracellular matrix ( 175 , 176 ). In a retrospective study, LAIR1 expression was found to associate to poor prognosis in invasive breast carcinoma ( 177 ), but also to resistance to PD1/PD-L1 inhibition in patients ( 178 ). Of interest, LAIR1 blockade by antagonist antibodies inhibited tumor development in a humanized mouse model by affecting, among others, the recruitment of pro-tumorigenic pDCs ( 179 ).…”
Section: Irs Expressed By Pdcs and Their Role In Physiology And Tumorsmentioning
confidence: 99%